Fluidodinâmica de leitos fluidizados e vibrofluidizados operando com partículas planas - Lima, Renata de Aquino Brito (Universidade Federal de São Carlos, 2009)
The use of fluidized beds as a unit operation for drying of particulate materials is common in industrial processes. However, most works published in the literature, focus the drying of uniform particles, in a narrow range of size distribution. The appealing characteristics of fluidization for drying led some authors to suggest its use for drying of particles of low sphericity (_ < 0.5), which are out of the range of usually fluidized particles. Aiming to contribute for the assessment of fluid dynamic behavior of this class of particles, in the present work was investigated the fluidization of flat particles, with _ varying from 0.063 up to 0.574, bulk density (b) from 0.038 to 0.923 g.cm-3 and ratios Ap/Vp (superficial area to volume) between 12 and 226 cm-1. The essays were carried out in a fluidized bed with a height of 0.30 m, and cross section of 0.20 m x 0.11 m, which could be also operated as a vibro-fluidized bed. The tests aimed to investigate the effects of size, shape and specific mass of particles in fluidization and fluid-dynamic behavior of such particles. Vibro-fluidization was tested as an alternative to improve fluidization patterns. Fluid dynamic characteristic curves of P as a function of air velocity were also obtained for the fixed beds in order to evaluate the resistive parameters of these beds as a way to quantify their resistance to the air flow. Tests were conducted using 14 different particulate materials, 9 of them being natural particles (leafs, seeds and cereals) and 5 being manufactured particles. The use of manufactured particles allowed to minimize size distribution and shape variations that are inherent to the natural products, avoiding interfering effects that might complicate an initial analysis. The fluid dynamic behavior was investigated through experimental curves of _P versus U and visual observation of the beds. The results showed that only the particles with sphericity around 0.5 and low ratios Ap/Vp presented homogeneous fluidization patterns, similar to the observed in fluidization of conventional particles. In fluidization of particles with _ 0.228 were observed poor fluidization patterns and highly non-homogeneous beds. The values of bulk porosity of static beds were higher than 80% for the beds constituted by leaves, and stayed between 30 and 70% for the remaining particles. The values of _b and _mf tended to decrease as the values of Ar increased, while Pmf tended to increase and Umf showed no clear dependence of Ar. The use of vibration did not reduce significantly the values of Umf and did not improve much the quality of fluidization as well, excepting for the particles of higher sphericity (around 0.5). But for some conditions obtained as fluidizing rigid particles, with large superficial areas, the vibration did provoke the alignment of particles into the beds, leading to a packing in which the contact area between particle and fluid is optimized, which might be interesting as drying applications are concerned.
Keywords: Fluidização; Leito vibrofluidizado; Esfericidade; Partículas de biomassa; ENGENHARIAS::ENGENHARIA QUIMICA